Association Between Posttraumatic Stress Disorder and Epigenetic Age Acceleration in a Sample of Twins. Issue 2 (11th February 2022) - Wang, Zeyuan; Hui, Qin; Goldberg, Jack; Smith, Nicholas; Kaseer, Belal; Murrah, Nancy; Levantsevych, Oleksiy M.; Shallenberger, Lucy; Diggers, Emily; Bremner, J. Douglas; Vaccarino, Viola; Sun, Yan V.
Abstract : Posttraumatic stress disorder (PTSD) may physiologically induce accelerated aging, which can be objectively measured by DNA methylation age acceleration. We investigated the association of a clinical diagnosis of PTSD and symptom severity of PTSD with six measurements of DNA methylation age acceleration. We observed that twins with current PTSD were "epigenetically older" than their twins without PTSD. The association between PTSD and epigenetic age acceleration was primarily through unshared environmental mechanisms as opposed to genetic or familial factors. Supplemental digital content is available in the text. ABSTRACT: Objective: Posttraumatic stress disorder (PTSD) has been related to accelerated biological aging processes, but objective evidence for this association is limited. DNA methylation (DNAm) age acceleration is a novel measure of biological aging that may help clarify if PTSD is related to biological aging processes. We aim to examine whether PTSD is associated with biological aging using a comprehensive set of DNAm age acceleration markers and to what extent the unshared environment contributes to the association. Methods: Using a cross-sectional co-twin control study design, we investigated the association of the clinical diagnosis and symptom severity of PTSD with six measurements of DNAm age acceleration based on epigenome-wide data derived from peripheral blood lymphocytes of 296 male twins from the Vietnam Era Twin Registry. Results: Twins with current PTSD had significantly advanced DNAm age acceleration compared with twins without PTSD for five of six measures of DNAm age acceleration. Across almost all measures of DNAm age acceleration, twins with current PTSD were "epigenetically older" than their twin brothers without PTSD: estimated differences ranged between 1.6 (95% confidence interval = 0.0–3.1) and 2.7 (95% confidence interval = 0.5–4.8) biological age year-equivalents. A higher Clinician-Administered PTSD Scale score was also associated with a higher within-pair DNAm age acceleration. Results remained consistent after adjustment for behavioral and cardiovascular risk factors. Conclusions: PTSD is associated with epigenetic age acceleration, primarily through unshared environmental mechanisms as opposed to genetic or familial factors. These results suggest that PTSD is related to systemic processes relevant to biological aging.